Methylglyoxal attenuates isoproterenol-induced increase in uncoupling protein 1 expression through activation of JNK signaling pathway in beige adipocytes - Su-Ping Ng (Biochemistry and Biophysics Reports, 2021)
Methylglyoxal (MG) is a metabolite derived from glycolysis whose levels in the blood and tissues of patients with diabetes are higher than those of healthy individuals, suggesting that MG is associated with the development of diabetic complications. However, it remains unknown whether high levels of MG are a cause or consequence of diabetes. Here, we show that MG negatively affects the expression of uncoupling protein 1 (UCP1), which is involved in thermogenesis and the regulation of systemic metabolism. Decreased Ucp1 expression is associated with obesity and type 2 diabetes. We found that MG attenuated the increase in Ucp1 expression following treatment with isoproterenol in beige adipocytes. However, MG did not affect protein kinase A signaling, the core coordinator of isoproterenol-induced Ucp1 expression. Instead, MG activated c-Jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinases. We found that JNK inhibition, but not p38, recovered isoproterenol-stimulated Ucp1 expression under MG treatment. Altogether, these results suggest an inhibitory role of MG on the thermogenic function of beige adipocytes through the JNK signaling pathway.